The Dilemma of Restorative Justice in the Case of Plantation Land Fires - Kurnia Dermawan, Aji; Mustakim, Mustakim (Journal of Law, Politic and Humanities, 2024)
The haze disaster due to plantation fires that has long occurred in a number of regions in Indonesia, apart from being exacerbated by extreme drought, there are also deliberate factors both individuals and corporations for land preparation. A vindicative justice approach that punishes the perpetrators with severe penalties has been implemented. Ironically, fires continue to recur almost every year. The Covid-19 pandemic and the adoption of the omnibus law have finally encouraged a new paradigm of law enforcement oriented towards economic recovery by prioritizing restorative justice oriented towards non-penal sanctions. This research is a qualitative doctrinal legal research with a statute and case approach. The results show that the application of restorative justice in the case of plantation land fires is not possible because it is included in an excluded environmental crime. The application of restorative justice in plantation fire cases needs to be done selectively, namely only for negligence that does not cause harm to people and significant environmental damage. In addition, smallholders, traditional farmers, and indigenous peoples are entitled to a fair settlement of land fire cases based on the principles of restorative justice and local wisdom.